Thor the mighty avenger - Langridge, Roger 1967-; Wilson, Matthew (Marvel Worldwide, 2023)
"It's Thor as you've never seen him before! Eisner and Harvey Award-nominated writer Roger Langridge and artist Chris Samnee reimagine the God of Thunder! Thrill as Thor faces the mischievous machinations of his adopted brother, Loki, battles raging robots the size of cities and fights side-by-side with Iron Man for the first time! Gasp as he tames the mightiest sea creatures and tests his might against the Sub-Mariner! Swoon as he rescues damsels in distress from the vilest villains! And chuckle as the Son of Odin finds his way in a strange world - with Jane Foster as his guide! Featuring the Warriors Three and the fearsome Fin Fang Foom! Plus: Loki's machinations throw Thor and a World War II-era Captain America into King Arthur's court in a time-twisting tale of Camelot craziness!"--Amazon.com